Basic education. Beyond compulsory and free education - Pérez Aguilar, José Francisco (Avances en Supervisión Educativa, 2022)
The modification of the LOE by the LOMLOE brings with it important changes in the conception and application of the curriculum in basic education, as the emergence of the Student Exit Profile at the end of basic education and the Universal Design for Learning demand practices in line with the performance of competences in a highly comprehensive and inclusive context. For this reason, this article aims to provide an exposition, focused on basic education, to analyse how this basic right transitions from its compulsory and free provision to the generation of conditions that guarantee continuity, coordination and cohesion between the two stages of basic education. Once universalisation has been achieved, it is then of interest to examine what students learn and how they are assessed, as well as the treatment of possible barriers that may impede learning.